X-3(-2)=5

Simple and best practice solution for X-3(-2)=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-3(-2)=5 equation:


Simplifying
X + -3(-2) = 5

Multiply -3 * -2
X + 6 = 5

Reorder the terms:
6 + X = 5

Solving
6 + X = 5

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + X = 5 + -6

Combine like terms: 6 + -6 = 0
0 + X = 5 + -6
X = 5 + -6

Combine like terms: 5 + -6 = -1
X = -1

Simplifying
X = -1

See similar equations:

| Log[4]6-log[4]-2x=1 | | (2X)-13=X+12 | | 7n+3(4n+8)=5 | | 3t-29=32+4t | | 4x+11y=213 | | X+12=(2*x)-13 | | 4.3x=4.3x | | 4y-32=12x | | (5x-1)+(2x+3)= | | 3y-10-15y=-6y+14 | | 4+8r=-4+7r | | 5.5x+7-1.5x=3.2-3 | | 3w+9=-15 | | X-3-6=-9 | | 5+[3]n=29 | | (11y+2)=130.42 | | 0.25+4=0.4(n+4) | | 2(-8+k)=18 | | f(-x)=4x^2-2x+8 | | 9(x^2+4x+4)=0 | | 3=3+5k | | v(j+y)=61y+82 | | -3=4-7r | | 6a^2-3.6a=0 | | 8x+6x=42 | | C^2+4x+4=0 | | 24(a-4)+13-3+55-9+44= | | -3(3r+6)+4(r+5)=-28 | | f(x)=-2x^2-10x+12 | | -4(x-8)-2(x+5)=70 | | 4p-12=-47+9p | | X-13=(.5*X)+12 |

Equations solver categories